The New ifo Business Climate Index for Germany - Stefan Sauer; Klaus Wohlrabe (CESifo Forum, 2018)
The ifo Business Climate Index is the most important early indicator for developments in the German economy. It aggregates thousands of responses from the companies surveyed in the ifo business surveys on a monthly basis. This article presents the new ifo Business Climate for Germany, which will appear on a monthly basis as of April 2018, replacing the index for German industry and trade that has been published to date. A few major changes have been made to the new business climate index. The most important change is that in addition to manufacturing, construction and both distributions sectors, it now includes the service industry, which has been published separately to date. Moreover, the aggregation procedure has been slightly modified, and finally the base year for index calculation has been adjusted from 2005 to 2015. This article offers an insight into the background to these adjustments and shows that the basic economic forecasts and interpretations remain unchanged.
Keywords: C22; O10; 330; Konjunktur; Wirtschaftsprognose; Frühindikator; Deutschland; Geschäftsklima